2022
DOI: 10.3390/ani12151950
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methionine Supplementation on Serum Metabolism and the Rumen Bacterial Community of Sika Deer (Cervus nippon)

Abstract: Methionine is the first or second limiting amino acid for ruminants, such as sika deer, and has a variety of biological functions such as antioxidant activity, immune response, and protein synthesis. This study aimed to investigate the effects of methionine supplementation on antler growth, serum biochemistry, rumen fermentation, and the bacterial community of sika deer during the antler-growing period. Twelve 4-year-old male sika deer were randomly assigned to three dietary groups supplemented with 0 g/day (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…The apparent digestibility of organic matter, NDF and ADF increased significantly in the LMet group under the experimental conditions, which was consistent with previous predictions for changes in nutrient utilization. A previous study found changes in the abundance of a variety of rumen bacteria associated with cellulose degradation, especially in the LMet group, which showed a significant increase, improving the animal’s ability to utilize crude fiber components in the feed [ 15 ]. It has also been shown that methionine supplementation had a positive effect on the fermentation rate of NDF in the rumen of heifers, which facilitated the utilization of cellulose by the animals [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent digestibility of organic matter, NDF and ADF increased significantly in the LMet group under the experimental conditions, which was consistent with previous predictions for changes in nutrient utilization. A previous study found changes in the abundance of a variety of rumen bacteria associated with cellulose degradation, especially in the LMet group, which showed a significant increase, improving the animal’s ability to utilize crude fiber components in the feed [ 15 ]. It has also been shown that methionine supplementation had a positive effect on the fermentation rate of NDF in the rumen of heifers, which facilitated the utilization of cellulose by the animals [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was preceded by a one-week pre-experiment and consisted of a four-week dietary treatment in June 2021. The deer in each group were fed a corn silage and concentrate based diet with a dry matter content of 35% to 65% [ 15 ]. Methionine was randomly added to the basal diet at 0 g/day (CON), 4 g/day (LMet) or 6 g/day (HMet).…”
Section: Methodsmentioning
confidence: 99%
“…At the genus level, Prevotella taxa were more abundant in the HMBi and MHA-Ca groups than in the Control group. Prevotella has been reported to be primarily involved in the degradation of proteins and carbohydrates [ 57 ]. It was found that Prevotella_1 was significantly positively correlated with DMD, MCP, and fermentation parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Proline is involved in numerous biological processes, including protein and amino acid synthesis, structure, nutrition, and immune response [39]. Methionine, on the other hand, plays important roles in metabolism, the immune system, antioxidant, and digestive function [40,41]. Cereals and legumes serve as primary food and feed sources for both humans and animals; however, they often lack adequate levels of certain essential amino acids, especially methionine and lysine [42].…”
Section: Discussionmentioning
confidence: 99%
“…In poultry diets, methionine stands out as an essential amino acid and is typically the first limiting amino acid [43][44][45]. This sulfur-containing amino acid is also a limiting amino acid in other animal feeds including fish and deer [41,46]. Arginine participates in diverse biological activities, such as protein synthesis, immune response, and nitric oxide production [47].…”
Section: Discussionmentioning
confidence: 99%